Reflections on Henrikas Nagys’ Life and Works in “Diary” - Babonaitė-Paplauskienė, Virginija (Respectus Philologicus, 2022)
The article discusses the “Diary” (1944–1946) by Henrikas Nagys (1920–1996), а diaspora poet, translator, literary critic, a member of a movement of zemininkai-lankininkai and Doctor of Humanities, as one of the objects of ego-documentary heritage, kept in the Maironis Museum of Lithuanian Literature. It records the period of one post-war year, which became a decisive turning point for his generation. Applying the descriptive and interpretive methods of analysis of the archival material, the philosophical, existential and personal aspects that have formed in the writer‘s mind are revealed; the historical, social and cultural context is assessed, revealing the value criteria of the generation. Via texts, the scenario of Henrik Nagys’ personality becomes clearer. The diary text in scientific discourse is revealed for the first time.